The Influence of the Panji Tales on the Lyrics of Bedhaya Ketawang - Michi Tomioka (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2022)
The lyrics of Bedhaya Ketawang have been interpreted too much in line with the romance of Ratu Kidul and a Mataram king, with a view that the written words convey the meaning of the dance performance. On the contrary, the meaning is often made up by later interpretation. If written words are examined without preconception, it is difficult to say the dance depicts romance. From the fact that Jayengsekar, another name of Prince Panji, appears in the lyrics of Bedhaya Ketawang, as well as that the lyrics resemble the texts of two different Panji Tales, it can be considered that the first section of Bedhaya Ketawang was taken from the Panji Tales. The Panji Tales were favoured by court people, and a script was prepared in case of the performance in the court, by which lyrics of the Panji Tales may have been collected in the court. Prince Panji and his wife had been the symbol of love since before the Mataram period; therefore, the lyrics of the Panji Tales may have been chosen to create the love-themed dance, which was later named Bedhaya Ketawang